2020
DOI: 10.1016/j.jneumeth.2019.108484
|View full text |Cite
|
Sign up to set email alerts
|

Companion animal models of neurological disease

Abstract: Clinical translation of novel therapeutics that improve the survival and quality of life of patients with neurological disease remains a challenge, with many investigational drug and device candidates failing in advanced stage clinical trials. Naturally occurring inherited and acquired neurological diseases, such as epilepsy, inborn errors of metabolism, brain tumors, spinal cord injury, and stroke occur frequently in companion animals, and many of these share epidemiologic, pathophysiologic and clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 286 publications
0
28
0
Order By: Relevance
“…On the other hand, dogs also represent a suitable translational animal model for comparable human diseases, for example spinal cord injury. 26,27 In conclusion, SGCs represent a fascinating cell population that expresses a wide variety of interesting markers. These features make them attractive candidates for ensuing in vitro studies and research addressing regenerative processes post-injury to, for example, the CNS/ PNS in particular.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, dogs also represent a suitable translational animal model for comparable human diseases, for example spinal cord injury. 26,27 In conclusion, SGCs represent a fascinating cell population that expresses a wide variety of interesting markers. These features make them attractive candidates for ensuing in vitro studies and research addressing regenerative processes post-injury to, for example, the CNS/ PNS in particular.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 99%
“…Dogs show comparable pathogenic mechanisms, lesion distribution and morphology as well as clinical manifestations. 26 , 27 , 28 A better understanding of cSGCs and their potential regenerative properties will be beneficial for future applications in regenerative medicine. The goal of this study is to provide a detailed phenotypical analysis of cSGCs in direct comparison to mSGCs.…”
Section: Introductionmentioning
confidence: 99%
“…Under the umbrella of the One Health Initiative, a growing number of investigations have integrated companion animals into preclinical studies to complement and expand the knowledge gained from studies in other animal models, accelerate and improve the framework in which research is translated to the human clinic, and ultimately generate discoveries that will benefit the health of humans and animals 6 . Over the last few years, several review articles have highlighted the benefits of using dogs for translational research in oncology, 7 neurology, 8 and other biomedical fields, 6 yet such information is not available in ophthalmology.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, several investigations have integrated companion animals into preclinical studies to expand the knowledge gained from studies in other animal models and generate discoveries that will benefit the health of humans and animals [ 26 ]. Some authors reported the benefits of using dogs for translational research in different biomedical fields such as oncology [ 27 ] and neurology [ 28 ]. In ophthalmology, the canine ocular anatomy is more similar to humans than small laboratory animals and some spontaneously occurring ocular surface diseases are comparable in both canine and human species [ 29 ].…”
Section: Introductionmentioning
confidence: 99%